Pengaruh Carbon Emission Disclosure terhadap Nilai Perusahaan dengan Sensitivitas Industri sebagai Variabel Moderasi: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Putri, Shinta Aulana; Sebrina, Nurzi (Universitas Negeri Padang, 2025)
This study aims to examine the effect of carbon emission disclosure on firm value with industrial sensitivity as a moderating variable in companies listed on the Indonesia Stock Exchange in 2019-2022. This research adopts a causal associative approach with quantitative methodology. The selection of a sample of 71 companies uses a purposive sampling method. The firm’s value as dependent variable is measured by Tobin's Q. Carbon emission disclosure as independent variable utilizes carbon disclosure checklist with consists of 18 disclosure items and industrial sensitivity as moderating variable based on industry high profile and low profile. The data analysis technique in this study used moderating regression analysis using the Eviews12 program. The result indicate that carbon emission disclosure has positive and significant effect on firm value, but industrial sensitivity correlation is not able to strengthen or weaken the relationship between carbon emission disclosure and firm value.